A Historical Research To Determine The Missing Link: The Untold Story Of Dato Che Wan Ahmad Pahang, The Warrior And The Strategist - Che Wan Chik Che Wan Ibrahim; Normazla Ahmad Mahir; Haliza Harun (Universiti Sains Islam Malaysia, 2024)
History of the Che Wans fiom 1850 to 1900 is centered on Che Wan Ahmad Tun Ali who was "banished" from Pahang and took shelter in Terengganu. From Terengganu, he made several forays into Pahang but failed to make lasting impact on the people until he made alliances with Che Wan Idris of Jelai, Wan Ahmad Tembeling, Tok Gajah and Baginda Omar, the Sultan of Terengganu. Revolt of the Rawa people led by Che Wan Abdul Rahman and Tok Gajah against Bendahara Mutahir gave Che Wan Idris of Jelai or Tok Raja as he was also known, an opportunity to return to Pahang fiom Kelantan with his men and led the uprising from Jelai to Tembeling. The fall of Tembeling to forces allied to Che Wan Ahmad brought the young prince back to Pahang with an army from Terengganu equipped by Baginda Omar. Soon Chenor, Pulau Manis and all territories south from Gancong to Pekan fell to their onslaught. Tun Mutahir died in Sedili and his son Tun Koris died in Kuala Pahang. The death of Mutahir marked the end of his reign and Che Wan Ahmad was declared the new Bendahara of Pahang. The implication of Che Wan Ahmad Temenggong of Tembeling and his abdication during Che Wan Ahmad's rule as Sultan of Pahang when Pahang was under the British Resident is a piece of history missing fiom Pahang. Che Wan Ahrnad Temenggong survived British imperialism and resurfaced in Kampong Che Wan, Kijal. The village bore the Che Wan's name until this day.